Modeling theory and the level of model complexity - Vogal, Lukas; Pecina, Miroslav (Vojnotehnički glasnik / Military Technical Courier, 2019)
This article deals with the level of detail and complexity of the model. The aim of the article is to find out what are the objective options for determining the optimal level of detail and complexity of the model. First, the basic concepts of the model and modeling are explained. Consequently, the concepts of complexity and level of detail are examined. One of the solutions to this problem is a fictitious model and a theory of model performance measurement.